2014
DOI: 10.5936/csbj.201402004
|View full text |Cite
|
Sign up to set email alerts
|

Open Questions in Origin of Life: Experimental Studies on the Origin of Nucleic Acids and Proteins With Specific and Functional Sequences by a Chemical Synthetic Biology Approach

Abstract: In this mini-review we present some experimental approaches to the important issue in the origin of life, namely the origin of nucleic acids and proteins with specific and functional sequences. The formation of macromolecules on prebiotic Earth faces practical and conceptual difficulties. From the chemical viewpoint, macromolecules are formed by chemical pathways leading to the condensation of building blocks (amino acids, or nucleotides) in long-chain copolymers (proteins and nucleic acids, respectively). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Internal sequence stretches for g+G+A+L and a+G+A+L tetramers demonstrated high sequence diversity after only 4 d of reaction. The observation of more diverse tetramers as the system evolved is consistent with the hypothesis that a vast array of sequences may have been present on the prebiotic earth before the initiation of template-directed peptide synthesis (47,48). When considering a prebiotic timescale, it seems reasonable to conclude that proto-peptides of short to moderate length would have had sufficient time to diversify into an innumerable set of sequences.…”
Section: Comparing Theoretical and Experimental Depsipeptide Sequencessupporting
confidence: 61%
“…Internal sequence stretches for g+G+A+L and a+G+A+L tetramers demonstrated high sequence diversity after only 4 d of reaction. The observation of more diverse tetramers as the system evolved is consistent with the hypothesis that a vast array of sequences may have been present on the prebiotic earth before the initiation of template-directed peptide synthesis (47,48). When considering a prebiotic timescale, it seems reasonable to conclude that proto-peptides of short to moderate length would have had sufficient time to diversify into an innumerable set of sequences.…”
Section: Comparing Theoretical and Experimental Depsipeptide Sequencessupporting
confidence: 61%
“…Histidyl-histidine (His-His) catalyzes the dephosphorylation of deoxyribonucleoside monophosphate, the hydrolysis of oligo (A) 12 , and the oligomerization of 2',3'-cAMP under cyclic wet-dry reaction conditions [ 25 ]. More recent studies have shown that seryl-histidine (Ser-His) catalyzes the oligomerization of trimers of imidazole-activated nucleotides [ 26 , 27 ], and catalyze peptide bond formation between two amino acids, an activity also found in seryl-histidyl-glycine (Ser-His-Gly) [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is worthwhile noting that polymerization of RNA from monomers and self-replication of small RNA units has received considerable attention from experimentalists (Bowler et al 2013;Adamala and Szostak 2013;Adamala et al 2014), including those looking for self-replication of RNA in extant organisms. The presence of an RNA template, say a small RNA polymer such as tRNA, may itself catalyze its own duplication by serving as a template for the assembly of a complementary strand from monomers in the surrounding medium.…”
Section: An Organic Carbon Rich Surface and The Source Of Primitive Tmentioning
confidence: 99%